2016
DOI: 10.1209/0295-5075/114/31001
|View full text |Cite
|
Sign up to set email alerts
|

New physics and signal-background interference in associated pp → HZ production

Abstract: We re-investigate electroweak signal-background interference in associated Higgs production via gluon fusion in the presence of new physics in the top-Higgs sector. Considering the full final state pp → bb + − ( = e, µ), we discuss how new physics in the top-Higgs sector that enhances the ZZ component can leave footprints in the HZ limit setting. In passing we investigate the phenomenology of a class of new physics interactions that can be genuinely studied in this process.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 116 publications
1
17
1
Order By: Relevance
“…[30,31] found that, in analogy to our results for gg → ZZ that will be presented in section 3, modifications of the top-Z interactions can have important effects on gg → hZ. A more careful comparison of the two processes is therefore postponed to section 3.4.…”
Section: Jhep09(2016)123supporting
confidence: 67%
See 3 more Smart Citations
“…[30,31] found that, in analogy to our results for gg → ZZ that will be presented in section 3, modifications of the top-Z interactions can have important effects on gg → hZ. A more careful comparison of the two processes is therefore postponed to section 3.4.…”
Section: Jhep09(2016)123supporting
confidence: 67%
“…Indeed, reinterpreting the results of ref. [31] we find 8 that the constraint on the (δc A , c g ) plane obtained from gg → hZ is somewhat stronger than the one from our gg → ZZ analysis, see the top left panel of figure 4. We also observe that, interestingly, the two constraints are approximately aligned, although the origin of this alignment is not transparent.…”
Section: Comparison To Other Gluon-fusion Processescontrasting
confidence: 53%
See 2 more Smart Citations
“…We leave instead a detailed phenomenological analysis for future work. For recent phenomenological work in the area a surely incomplete list is [20][21][22][23][24][25].…”
Section: Jhep06(2016)107mentioning
confidence: 99%